Computational Insight into the Mechanism of Mannich Reaction between Glycinate and Aryl N‐Diphenylphosphinyl Imine Catalyzed by N‐Quaternized Pyridoxal. Issue 21 (5th June 2020) - Yang, Yongsheng; Zhang, Yan; Yang, Junxia; Xue, Ying
Abstract: Recently, Chen et al. reported an asymmetric biomimetic Mannich reaction of tert ‐butyl glycinate (sub‐1 ) with aryl N ‐diphenylphosphinyl imine (sub‐2 ) catalyzed by N ‐quaternized pyridoxal analogue (cat ) (Chen et   al ., Science, 2018, 360, 1438–1442). By utilizing Gaussian 09 program, we provide the detailed density functional theory (DFT, including B3LYP−D3 and M06‐2X) investigations on the mechanisms of each section of the reaction with CHCl3 as implicit solvent. These cat, sub‐1 and OH − if it exists can act as catalytic base and need to overcome relative free energy barrier of ∼12, 13.5 and 4.2 kcal/mol, respectively, to achieve α‐carbon deprotonation. During the addition reaction, the most favorable transition structure was calculated to overcome a relative free energy barrier of 6.3 kcal/mol, verifying the bifunctional activation mode of cat . The final hydrolysis reaction starts with hydration to achieve protonation at the N atom of sub‐2 portion and generates a carbinolamine. These computational results help one obtain deep understanding of the reaction mechanism and benefit future design of pyridoxal catalyst and similar biomimetic reaction. Abstract : The pyridoxal‐catalyzed Mannich reaction between tert ‐butyl glycinate and aryl N ‐diphenylphosphinyl imine, was studied by Density Functional Theory (DFT) method. The specific deprotonation processes were figured out to achieve α ‐carbon deprotonation which is activated by pyridoxal catalyst. Phenolic oxyanion, tert ‐butyl glycinate, and OH − can act as catalytic base. During addition reaction for C−C bond formation, N ‐diphenylphosphinyl imine establishs strong hydrogen‐bonding interaction with side arm chain of pyridoxal catalyst.